KUALITAS PELAYANAN BAR WAITER DI LOBBY LOUNGE EMERALD GARDEN INTERNATIONAL HOTEL MEDAN - Vero Valentina Sihaloho; Andi Moh Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research aims to know the service quality of bar waiter at Lobby Lounge Emerald Garden International Hotel Medan. The role of bar waiter in creating good quality service is very influential on guest satisfaction and increasing income,because bar waiter has a function as frontliner. The research method used is a quantitative research method based on data obtained from respondents. This research uses the concept (Zeithaml, 2004), saying to facilitate the assessment and measurement of quality service, therefore developed a quality service measuring tool called SERVQUAL (Service Quality). Servqual is a multiscale item which one can be used to measure customer perception of the quality service which includes: tangibles, reliability, responsiveness, emphaty, and assurance. Based on the research that has been done, service quality of bar waiter at Lobby Lounge Emerald Garden International Hotel Medan was good. Keywords: Service Quality, Bar, Waiter, Food And Beverage Service.